Health Condition of Tridacna sp. in the waters of Obi Island, Indonesia - Tamrin Tamrin; Muhammad Aris (Sam Ratulangi University, 2020)
Tridacna sp. is one of the protected heritage in Indonesia, because its population has declined dramatically. Tridacna sp. is the largest type of shellfish in water. Like a clam, Tridacna sp. can be used as a bioindicator of the aquatic environment because it can accumulate more heavy metals than other aquatic organisms due to its nature as a filter feeder. This study aims to determine the health condition of Tridacna sp. in the waters of Obi Island with a histopathological analysis approach. The histopathological analysis aims to see the level of tissue damage due to the accumulation of heavy metals. Observation of water quality was also observed in this study. Water quality parameters observed in-situ are temperature, brightness, salinity, pH, and dissolved oxygen. While the water quality parameters observed ex-situ are nitrate, orthophosphate, ammonia, iron (Fe), and nickel (Ni). Observations show that the water temperature is at 27.99 â„ƒ. Water brightness is at 13 m. Salinity is at 32.13 mg / l. The acidity of the waters is 8.64. Ammonia is at 0.4 mg / L. Nitrate is at 0.009 mg / L. Orthopedics are at 0.016 mg / L. Dissolved oxygen waters are at 3.77 mg / L. The iron (Fe) level of water is at 0.6 mg / L. The level of nickel (Ni) waters is at 0.06 mg / L. This study shows the health condition of Tridacna sp. the histological approach shows that the condition of the network has changed. Symptoms of this change indicate the condition of the Tridacna sp. degeneration and cell necrosis. This change is thought to be influenced by heavy metals. Heavy metal content in liquids exceeds the quality standard threshold.Keywords:Â Tridacna sp.; Heavy metal; Water quality; histopathological.